Weathering - Benitez, Christian Jil Repalda (SARE: Southeast Asian Review of English, 2024)
Short lyric poem meditating on "love... [and] uselessness of / its implications," considered from the scale of geological time, beside, for instance, a "boulder being itself on the face / of weathering."